OPTIMIZACIÓN DEL PROCESO DE ELABORACIÓN DE CUBETAS DE CARTÓN PARA HUEVOS EN LA EMPRESA PULPA MOLDEADA S.A. PARROQUIA TANICUCHÍ - Costales Tapia, Darío Paúl (2018)
The purpose of this research is to optimize the process for the production of egg cartons from the company PULPA MOLDEADA SA, in order to improve its efficiency and productivity through quality tools. In the research, the productive system was examined, the productive efficiency, with indicators the information of the current operation and production process, in order to suggest an improvement proposal. The proposed study is planned as a non-experimental research and a field modality is adopted, applying tools such as observation and documentary review to optimize the production process of the company PULPA MOLDEADA S.A. Next, the optimization of the process is suggested by means of the implementation electric key with rotating mechanical arm structure for the unloading of raw material with an improvement plan for the operation and control. This work allowed analyzing practical cases to improve the productivity in the elaboration of cardboard buckets.